Young Women between Cosmopolitan Dreams and Conservative Realities in the Russian Caucasus - Heemeryck, Antoine (Sensus Historiae, 2021)
This article is a reflection based on a survey of female students in the Russian Caucasus, torn between the desire to live in a cosmopolitan world and the respect for patriarchal standards revitalized in recent years in this region. This return is closely linked to the position of women in the Greater Russia project, which presupposes a demographic recovery and opens the door to conservative institutions in terms of morals.